Peran Literasi Budaya dan Kewarganegaraan guna Melestarikan Kebudayaan Nusantara di Era Modernisasi - Faishal Ridho; Su’aidi Hariyanto; Sulis Tia Ningsih; Mas’odi (FKIP, Universitas Palangka Raya, 2025)
The progress of the world in the era of modernization over time has a negative effect on the preservation of the Indonesian culture which can damage the preservation of culture and existing cultural values. The development of science and technology followed by the era of modernization that attacks the Indonesian culture has an impact on the people so that they are easily attracted to foreign cultures. By using qualitative research methods followed by literature studies, this explanation was created to explain the position of cultural and citizenship literacy in order to preserve the culture in Indonesia in the era of modernization. This can be applied by implementing cultural and citizenship literacy universally in the community environment and educational institutions. With this, the preservation of the Indonesian culture is maintained. The value of the Indonesian culture must be implemented in the real world and defended, because it is a symbol of the Indonesian state that remains.